2016
DOI: 10.1097/iop.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Eyelid Margin Malpositions: A Unique Spectrum in a South-East Asian Tertiary Hospital

Abstract: This study shows that the spectrum of eyelid margin malpositions in Singapore is unique and that developmental epiblepharon remains the commonest eyelid margin malposition requiring surgery. In terms of involutional eyelid margin malpositions, entropion is more common than ectropion, especially among the Chinese. The similarity in terms of eyelid involvement and ethnic distribution of both epiblepharon and involutional entropion suggests that there is a common factor in both these conditions, which the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…24,26 It is also unique regarding the type of population, namely Caucasian and Latin subjects, compared with Chinese, 25 Japanese, 17 Pakistani 26 or Bangladeshi 7 subjects in the prior studies. Previous studies have already reported the anatomical differences between oriental and occidental population, 27,28 something that makes difficult the extrapolation of the results from one ethnics to others.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 It is also unique regarding the type of population, namely Caucasian and Latin subjects, compared with Chinese, 25 Japanese, 17 Pakistani 26 or Bangladeshi 7 subjects in the prior studies. Previous studies have already reported the anatomical differences between oriental and occidental population, 27,28 something that makes difficult the extrapolation of the results from one ethnics to others.…”
Section: Discussionmentioning
confidence: 99%